Early retirement : free choice or forced decision - David Dorn; Alfonso Sousa-Poza (Center for Economic Studies and ifo Institute (CESifo), 2005)
Early retirement is usually explained as a supply-side phenomenon. However, early retirement can also be a demand-side phenomenon arising from a firm's profit maximization behavior. This paper analyzes voluntary and involuntary early retirement based on international microdata covering 19 industrialized countries. The results indicate that generous early retirement provisions of the social security system do not only make voluntary early retirement more attractive for individuals, but also induce firms to encourage more employees to retire early. In particular, firms seem to use early retirement to reduce staff during economic recessions and as a means to circumvent employment protection legislation.
Keywords: J26; J22; J21; J14; 330; early retirement; involuntary early retirement; social security; pensions; Flexible Altersgrenze; Arbeitsangebot; Personalabbau; Schätzung; Industriestaaten